Inovativnost v stanovanjski gradnji in vloga stanovanjskega sklada - Mlinar, Zdravko (Urbani izziv, 2008)
This article attempts to contribute to clarification of the conditions and actors impacting innovativeness in housing construction and the management of space. It concentrates on the role of the Slovenian national Housing Fund, which is too restricted and lacks appropriate legal bases and means, and also- according to some evaluations - the aspiration to assert its innovative and developmental role. The Fund is focussed on the financial-economic aspects of providing non-profit housing and housing for the market. Currently attention is primarily directed towards its legal-organizational structure and its transformation into an independent company. This neglects broader consideration of socio-spatial change, developmental directions and values in the context of the information age (Lisbon Strategy), which call for innovative sociological, architectural and urbanistic solutions. Mindsets, legal norms and institutions in Slovenia are lagging behind these changes. Thus, housing is still mainly treated as a discrete segment. In order to perform their task in this new framework, which demands more integral treatment of the everyday living environment and reintegration of living, work and recreation, the mandate of the housing fundsmust no longer be confined merely to housing. Several examples of innovative design as well as their limitations are presented, together with examples of good international practice.
Keywords: bivalno okolje; družbeni razvoj; prostorski razvoj; prostorsko urejanje; Slovenia; Slovenija; spremembe; stanovanjska arhitektura; stanovanjska naselja; stanovanjska politika; stanovanjske zgradbe